2005
DOI: 10.1002/adma.200401474
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene‐Functionalized Cationic Polythiophene for the Label‐Free Electrochemical Detection of DNA

Abstract: Many efforts have been made worldwide to develop and improve electrochemical methods for DNA detection with the aim of making portable and affordable devices.[1±4] In spite of many advances in this field, it is still a challenge to find new approaches that could improve the simplicity, selectivity, and sensitivity of DNA detection, in order to respond to the demands and needs of modern medical diagnostics and biomedical research applications. In this regard, some oligonucleotide-functionalized conjugated polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 20 publications
(3 reference statements)
1
88
0
Order By: Relevance
“…[10][11][12][13][14] Furthermore, the high selectivity of PNAs to detect even single RNA or DNA mismatches, has led their use in the biosensing area. [15][16][17][18] For this purpose, PNAmetal conjugates are particularly useful as they can act as electroactive and/or photoactive probes. Due to its well-3:2 ratio, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Furthermore, the high selectivity of PNAs to detect even single RNA or DNA mismatches, has led their use in the biosensing area. [15][16][17][18] For this purpose, PNAmetal conjugates are particularly useful as they can act as electroactive and/or photoactive probes. Due to its well-3:2 ratio, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that even visual detection with naked eyes could detect as few as 100 pM target DNA, which was comparable to or even better than many previously reported instrument-based DNA analysis. [25][26][27][28] Moreover, a detection limit in the low pM range was obtained by using a fluorescent approach. Also of note, there are several straightforward approaches to further improve this sensitivity in order to meet high-end applications, which include the use of large-size AuNPs that should carry more HRP molecules and bring about larger amplification; automated operation may lead to better reproducibility; and the use of electrochemical detection for HRP-catalyzed reactions may lead to higher sensitivity.…”
mentioning
confidence: 99%
“…Poly(ferrocenyl)-based macromolecules have been demonstrated to possess useful properties for the chemical modification of electrodes and also as electrochemical sensors and electrode mediators in biosensors [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%